PENGARUH PENGETAHUAN INVESTASI, MANFAAT INVESTASI, MOTIVASI INVESTASI, MODAL MINIMAL INVESTASI DAN RETURN INVESTASI TERHADAP MINAT INVESTASI DI PASAR MODAL ( Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Mataram ) - H. Burhanudin; Sri Bintang Mandala Putra; Siti Aisyah Hidayati (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
This research was conducted with the aim to examine the effect of variable Investment Knowledge, Investment Benefit, Investment Motivation, Investment Capital Minimum and Investment Return on Investment Interest in Capital Market Study in Faculty of Economics and Business University of Mataram Student. This type of research is a associative research with quantitative methods. The sample in this study was obtained by cluster sampling method. Based on the existing criteria, there were 60 student of Faculty Economics and Business which is the sample in this study is 36 Accounting Student, 18 Management student and 6 Economics Student that became the study sample. The data source used in this study is primary data, the data analysis technique used is multiple linear regression. The results showed that the Investment Knowledge, Investment Motivation and Investment Minimum Capital whose coefficients are positive but have no significant effect on Investment Interest. Other variable in this research Investment Benefits and Investment Return coefficient was positive and significant towards the Investment Interest. Based on the results of the F test showed that the feasibility in the model obtained a significance value of 0,000 <0.05, indicating that the test model is feasible to be used in research. The predictive ability of the five variables on the Investment Interest of 50.5% as shown by the size of the adjusted R square of 0.505 while the remaining 49.5% is explained by other factors not included in the research model.